Sum

Without using trigonometric tables evaluate the following:

`(i) sin^2 25º + sin^2 65º `

Advertisement Remove all ads

#### Solution

(i) We have,

`sin^2 25º + sin^2 65º = sin^2 (90º – 65º) + sin^2 65º`

`= cos265º + sin265º = 1`

[∵ sin (90º – θ) = cos θ]

(ii) We have,

`cos^2 13º– sin^2 77º = cos^2 (90º – 77º) – sin^2 77º`

`= sin^2 77º – sin^2 77º = 0`

[∵ cos (90º – θ) = sin θ]

Concept: Trigonometric Ratios of Complementary Angles

Is there an error in this question or solution?

Advertisement Remove all ads